Training technical or non-technical skills: an arbitrary distinction? A scoping review - Maria Louise Gamborg; Lisa Beicker Salling; Jan Duedal Rölfing; Rune Dall Jensen (BMC Medical Education, 2024)
Abstract Introduction Medical education often aims to improve either technical skills (TS) or ‘non-technical skills’ (NTS) and how these skills influence adverse events and patient safety. The two skill sets are often investigated independently, and little is known about how TS and NTS influence each other. In this scoping review, we therefore aim to investigate the association between TS and NTS. Method We conducted a scoping review of four databases in order to summarize, analyse, and collate findings from the included studies. Results In total, 203 of 2676 identified studies were included in the final analysis. The first study was published in 1991, but the majority of studies were published in the last decade. The majority were intervention studies including 41 randomized controlled trials. The the objective structured assessment of technical skills (OSATS) was the most common assessment tool with strong validity evidence within TS, but many variations without validity evidence were used. Conversely, Non-Technical Skills for Surgeons (NOTSS) was the most used tool with strong validity evidence for assessing NTS. However, the majority of studies used non-validated self-assessment tools to investigate NTS. The correlation between TS and NTS was assessed in 46 of 203 studies, whereof 40 found a positive correlation. Discussion Our findings echo previous literature suggesting that empirical literature investigating the interaction between TS and NTS lack methodological depth. In this review only a minority of the identified studies (n = 46) investigated this correlation. However, the results strongly indicate a correlation between TS and NTS skills, suggesting that physicians who are proficient in their NTS, also perform well on their TS. Thus, the distinction between them in learning designs may seem arbitrary. While this result is promising, the limited methodological rigour indicates a lack of proper understanding of NTS and how to properly assess them.